1986
DOI: 10.1016/s0735-1097(86)80287-x
|View full text |Cite
|
Sign up to set email alerts
|

Tachyarrhythmias in young athletes

Abstract: Nineteen young athletes with documented symptomatic tachyarrhythmia were systematically evaluated. There were 15 men and 4 women, aged 14 to 32 years (mean 22 +/- 6). Documented tachyarrhythmias were paroxysmal atrial fibrillation in five patients, paroxysmal supraventricular tachycardia in five, paroxysmal ventricular tachycardia in eight (sustained in five, nonsustained in three) and ventricular fibrillation in one patient. Abnormal substrates were demonstrated in 15 (79%) of the 19 athletes: 5 had an anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Five of 19 athletes evaluated for palpitations had paroxysmal AF,25 and were evaluated by resting electrocardiography, echocardiography and electrophysiological studies. Mitral valve prolapse (MVP) was reported in four athletes and WPW syndrome in one.…”
Section: Frequency Of Atrial Fibrillation In Athletesmentioning
confidence: 99%
“…Five of 19 athletes evaluated for palpitations had paroxysmal AF,25 and were evaluated by resting electrocardiography, echocardiography and electrophysiological studies. Mitral valve prolapse (MVP) was reported in four athletes and WPW syndrome in one.…”
Section: Frequency Of Atrial Fibrillation In Athletesmentioning
confidence: 99%
“…Although vigorous exercise has numerous health benefits, case reports and limited data suggest that male elite athletes engaging in endurance exercise that enhances parasympathetic tone, particularly jogging, may be at higher risk for the development of atrial fibrillation (AF) 1,2,3. There are limited data on the role of vigorous exercise in the development of AF among men participating in exercise at a less competitive level, where the known beneficial effects of exercise may counter balance this potential risk.…”
mentioning
confidence: 99%
“…Thirdly, a treadmill or ergometer exercise test provoked supraventricular tachycardia in only one patient. This low rate of provocation of tachycardia with an exercise test might be because exercise was not as strenuous as that reported by Coelho et al 6 Finally, the mechanism of palpitation in patient 8 remained uncertain. We should have tested a higher dose of isoprenaline infusion.…”
Section: Limitationsmentioning
confidence: 73%
“…Electrophysiological data on cases of exercise related supraventricular tachycardia are limited.68 Coelho et al reported that four of five cases of exercise related supraventricular tachycardia had an atrioventricular accessory pathway and atrioventricular reentrant tachycardia.6 Shortening of the atrioventricular nodal refractory period by isoprenaline and atropine was necessary to sustain supraventricular tachycardia in one and two cases respectively.6 In two of five patients in Coelho et al's study supraventricular tachycardia occurred only during treadmill exercise at a high level. 6 Akhtar et al reported on five cases of atrioventricular nodal reentrant tachycardia induced only by programmed stimulation after atropine injection." In three of five cases, the anterograde limb of the atrioventricular nodal reentrant pathway was refractory to the reciprocating impulse in the control state and atropine was required to reduce the refractory period of the atrioventricular node sufficiently to permit continuous reciprocation.…”
Section: Discussionmentioning
confidence: 99%